"Some were certainly better than others" – Bereaved parents' judgements of healthcare providers in the paediatric intensive care unit: A grounded theory study. (April 2018) - Butler, Ashleigh E.; Copnell, Beverley; Hall, Helen
Abstract: Objective: To explore bereaved parents' judgements of healthcare providers, as part of a larger study examining their perceptions of the death of a child in the paediatric intensive care unit. Research methodology: Constructivist grounded theory. Setting: Four Australian paediatric intensive care units. Main outcome measures: Semi-structured, audio recorded interviews were undertaken with 26 bereaved parents 6–48 months after their child's death. Data were transcribed verbatim and analysed using open, focused and theoretical coding and the constant comparative method. Findings: Bereaved parents judged healthcare providers as 'good' or 'poor' based on behaviours they exhibit. 'Good' behaviours were further subdivided by parents into four categories: 'Better than others', 'good', 'very good', and 'fantastic'. Common behaviours identified as 'good' included provision of practical assistance, facilitation of parental presence, and sharing of information. In contrast, the concept of 'poor' had no subdivision: all identified behaviours, including diminishing parental concern, mishandling hope, adopting an unprofessional demeanour, judging the child's worth, and mishandling communication, were equally detrimental. Conclusions: Findings demonstrate that bereaved parents have clear opinions on what constitutes 'good' and 'poor' behaviours when their child is dying. These judgements provide clear examples for healthcare providers who provide end-of-life care, ensuring they provide high quality care.